2022
DOI: 10.1007/s12028-022-01499-y
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Vinpocetine as a Neuroprotective Agent in Acute Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: Background Vinpocetine as a neuroprotective agent is effective in acute ischemic stroke in some randomized controlled trials (RCTs). Since the last systematic review has been published in 2008, which didn’t find conclusive evidence favoring its use, two more RCTs have also been completed. Methods Relevant electronic databases were searched with a suitable combination of Medical Subject Headings terms to detect publications describing RCTs exploring the safety and effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…Vinpocetine is indicated as an adjuvant treatment for chronic CNS disorders of cerebral circulation in the elderly, impairment of hearing, neurological disorders such as memory disorders, and post‐stroke impairment. It also improves vision disorders associated with impaired circulation of the choroid and retina of the eye 88,110–112 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vinpocetine is indicated as an adjuvant treatment for chronic CNS disorders of cerebral circulation in the elderly, impairment of hearing, neurological disorders such as memory disorders, and post‐stroke impairment. It also improves vision disorders associated with impaired circulation of the choroid and retina of the eye 88,110–112 …”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of phosphodiesterases (PDEs) in the cells of vascular walls causes an increase in the concentration of cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP) and, consequently, relaxation of smooth muscles and vasodilation. Vinpocetine is well absorbed from the gastrointestinal tract with approximately 60% absorption, and its biological half‐life is estimated to be 5–6 h. In the human body, vinpocetine is metabolized primarily by the liver into apovincaminic acid 110–112 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this situation, vinpocetine has not been accepted by clinicians for universal routine use for any neurological disorder. A systematic review found promising yet inconclusive evidence favoring its use in patients with dementia ( Panda et al, 2022 ). The discovery of a novel, natural, and nontoxic treatment for AD remains a great need ( Nabavi et al, 2019 ).…”
Section: Pde1 Inhibitors and Admentioning
confidence: 99%
“…These effects were found in geriatrics who were affected by vascular dementia in the subcortical region and need to be elucidated in large-scale trials with other groups ( Tomassoni et al, 2008 ). A double-blinded study recommended the routine prescription of vinpocetine; however, vinpocetine has not progressed to placebo-controlled randomized clinical trials with a particular sample size ( Panda et al, 2022 ). Vinpocetine remains extensively used as a nootropic owing to its memory-boosting effect, which may be correlated with its vasodilating effect.…”
Section: Conclusion and Later Prospectsmentioning
confidence: 99%